O-014 Intravascular high frequency optical coherence tomography guided WEB aneurysm embolization. (4th August 2020) - Vardar, Z; King, R; Kraitem, A; Langan, E; Peterson, L; Duncan, B; Raskett, C; Anagnostakou, V; Gounis, M; Puri, A; Ughi, G
Abstract : Introduction: High Frequency Optical Coherence Tomography (HF-OCT) 1 is an intra-vascular imaging technique to assess device-vessel interactions and neointimal tissue growth at unprecedented spatial resolution (~10µm). In this study, we tested the hypothesis that an adequately deployed (as visualized by HF-OCT) Woven EndoBridge (WEB, Microvention, Aliso Viejo, CA) will lead to a higher aneurysm occlusion rate at 12-week follow-up in an animal model of aneurysms. Methods: Elastase-induced rabbit aneurysms (n=24) were treated with the WEB device. HF-OCT (Vis-M; Gentuity LLC, Sudbury MA) and DSA were performed after WEB deployment and repeated at 4, 8, and 12 weeks. Protrusion and malapposition were binary coded (0- present, 1- absent; 0- malapposed, 1- neck apposition >50%), respectively, on HF-OCT and DSA. A device was considered adequately deployed if it was scored as 1 on both metrics. Aneurysm healing on DSA was interpreted using the 4-point WEB occlusion score (WOS) 2 ; with A-B considered a positive outcome. HF-OCT images acquired at 12 weeks were analyzed and neointimal coverage quantified. Scanning electron microscopy (SEM) was performed of the explanted specimens. Results: Discrepancy between HF-OCT and DSA was found: HF-OCT classified as adequately deployed a total of 5 cases, whereas 8 cases were classified as adequately deployed by DSA images. Acceptable WOS grade at 12 weeks was seen in 21% of cases (n=5): 80% of those cases (n=4) were classified as adequately deployed based by HF-OCT; whereas only 60% of those cases (n=3) classified adequate by DSA. A significant interaction between adequate deployment on HF-OCT and positive outcome was confirmed ( p= 0.007). However, there was no statistically significant relationship between good outcome and adequate deployment based on DSA images ( p= 0.289 ). Based on HF-OCT images, the absence of the protrusion was related with a positive outcome ( p= 0.006 ); however, malapposition had no significant interaction with positive outcome ( p= 0.19 ). The area of neointimal tissue quantified by HF-OCT showed a strong correlation with SEM assessment (R²=0.96 ; p< 0.001 ). The mean neointimal coverage on 'adequate deployment' cases was 78%, whereas a mean neointimal coverage of 31% was found for the 'not adequate deployment' cases ( p = 0.001 ). Conclusion: HF-OCT may be valuable prognosticate adequate aneurysm occlusion with the WEB and can be used to monitor aneurysm healing longitudinally. Absence of protrusion was associated with subsequent aneurysm occlusion; however, malapposition alone did not show an effect on the rate of aneurysm healing. Reference: Stroke. 2018:Nov29:STROKEAHA118022315 2. AJNR 2014;35:432–8. Disclosures: Z. Vardar: None. R. King: None. A. Kraitem: None. E. Langan: None. L. Peterson: None. B. Duncan: None. C. Raskett: None. V. Anagnostakou: None. M. Gounis: None. A. Puri: None. G. Ughi: None.